2017
DOI: 10.1111/ggi.12933
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and visualization of face‐to‐face interaction among community‐dwelling older adults using wearable sensors

Abstract: Social networks in the community are essential for solving problems caused by the aging society. We showed the possible applications of face-to-face interactional data for identifying core participants having many interactions, and isolated participants having only a few interactions within the community. Such data would be useful for carrying out efficient interventions for increasing participants' involvement with their community. Geriatr Gerontol Int 2017; 17: 1752-1758.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…This shows that community interventions using the resources of a university could strengthen older adults' neighborhood social networks. 17 According to national Japanese statistics, more than two-thirds of older adults do not have close relationships with their neighbors. 1-8 However, just a few studies have tried to strengthen older adults' social networks in community settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This shows that community interventions using the resources of a university could strengthen older adults' neighborhood social networks. 17 According to national Japanese statistics, more than two-thirds of older adults do not have close relationships with their neighbors. 1-8 However, just a few studies have tried to strengthen older adults' social networks in community settings.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the participants in our program can facilitate social interactions. 17 According to national Japanese statistics, more than two-thirds of older adults do not have close relationships with their neighbors. 15 Thus, many older adults would not have sufficient opportunities to communicate with their neighbors, and the intervention would offset the lack of such opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) ,利用者間のネットワーク 密度を高め,近隣の人々との相互作用への関心を高めた りする (Masumoto, Yaguchi, Matsuda, Tani, Tozuka, Kondo, & Okada, 2017)ことは示されている。 高齢者の精神的健康に関して,重要な示唆を与えてく れるのが,活動理論 (Lemon, Bengson, & Peterson, 1972…”
unclassified